(untitled) (Revista Innova Educación, 2025)
In an increasingly globalized world, job insecurity has increased in Latin America, affecting levels of social well-being. As a result, many families are trapped in a cycle of poverty from which it is difficult to escape. In this context, education becomes a key tool for improving quality of life. The objective of this study is to analyze the influence of parents’ precarious employment conditions on their children’s academic performance, with a particular focus on schools in the outskirts of Mazatlán, Sinaloa. Methodology: The study was exploratory in-depth with a qualitative approach, using a case study method. Data collection techniques included semi-structured interviews. Results: Although parents value educational attainment and have expectations about their children’s future employment, their perceptions are driven by their own precarious employment experiences. In conclusion, a relationship was identified between parents’ precarious employment conditions and students’ poor academic performance. These findings highlight the need for a multidisciplinary approach to addressing educational issues from a social perspective that considers the structural conditions that impact academic performance.